Impacts of environmental quality and employment resilience during the coronavirus disease 2019 recession and recovery - D.O. Ayuningsih; L. Hakim; A. Suryantoro; I. Mafruhah; S. Hassan; E. Gravitiani; N.Q. Fathoni; A.I. Hakim (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The unanticipated effects of the economic decline resulting from the coronavirus create both challenges and opportunities for assessing the ability of regions to achieve a balance between their economic demands and the preservation of the environment amidst the upheaval brought about by the pandemic. The objective of this study is to assess the spatial distribution of both the environmental quality index and the employment resilience index within the 34 provinces of Indonesia. This study examines the factors that may influence the environmental quality index during the recession and recovery periods due to coronavirus disease 2019.METHODS: The present study applies multiple linear regression techniques. The cross-sectional data for this analysis were acquired from the Central Bureau of Statistics, which includes information from 34 provinces in Indonesia during the years 2020 and 2021. This study compares the results of factors that influence the environmental quality index in the 2020 period when the recession was due to coronavirus (resistance dimension) with the 2021 period when the recovery was due to coronavirus (recovery dimension).FINDINGS: Employment resilience, gross regional domestic product rowth rate, technology and information, population, population density, and the coronavirus recovery rate influence the environmental quality index during the recession and recovery periods due to coronavirus disease 2019, with respective contributions of 75.02 percent and 83.59 percent. In the years 2020 and 2021, the environmental quality index predominantly fell within the good category; however, this distribution was not uniform across the 34 provinces in Indonesia. The categorization of economic resilience and recovery indicates that a majority of provinces in Indonesia are primarily characterized by the group exhibiting positive values in both economic resistance and recovery. Partially, during the recession and recovery periods due to coronavirus disease 2019, technology and information, population, and population density negatively impacted the environmental quality index. During the recovery intervals linked to the coronavirus disease 2019, the recovery index indicated a favorable influence on the environmental quality index.CONCLUSION: Employment resilience, gross regional domestic product rowth rate, technology and information, population, population density, and the coronavirus recovery rate influence the environmental quality index during the recession and recovery periods due to coronavirus disease 2019. Environmental quality index achievement remains uneven across the 34 provinces in Indonesia. Comparable findings indicate that the economic downturn resulted in diverse responses regarding employment resilience across different geographical areas. Numerous obstacles emerge in the pursuit of sustainable growth. The strategy involves fostering and bolstering support for the green economy, alongside promoting labor development in the renewable energy field, underpinned by heightened investment in green infrastructure.